Translation Strategies Of Idiomatic Expressions In Adele’s Album 25 - Putri, Kadek Adiva Prilia; Dewi, A.A. Sg. Shanti Sari; Laksminy, Luh Putu (Peneliti.net, 2026)
This study aims at identifying the types of idiom and analyzing the translation strategies used to render idiomatic expressions from English into Indonesian in Adele's album 25. A descriptive qualitative method was employed in this study. The data were collected through documentation method and note-taking techniques. Based on the findings, two types of idiom found in the song lyrics namely phrasal verb idiom and tournure verb idiom. In addition, three translation strategies were identified there are: using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, and translation by paraphrase.